Analysis of Pelvic Floor Muscles’ Self-Perception and the Presence of Urinary Symptoms among Women (Movimenta (ISSN 1984-4298), 2022)
Introduction: The female population, in general, has little knowledge of the pelvic floor muscles (PFM) and the changes that can cause dysfunctions. PFM knowledge is related to the ability to contract these muscles; which helps to avoid malfunctions. Objective: To investigate the perception and knowledge that women have about PFM; as well as investigate if they present urinary symptoms. Methods: A cross-sectional study was carried out where 89 women were recruited (mean age: 26±6.36 years). The volunteers answered an online questionnaire provided by the Google Docs platform, through which they were asked if they had knowledge and perception of PFM, as well as the urinary symptoms were investigated through the ICIQ UI-SF and ICIQ-OAB validated questionnaires. Results: It was found that 42.7% of the volunteers reported not having perception and knowledge of PFM. The mean mandatory score by the ICIQ UI-SF was 1.38 ± 0.2 and by the ICIQ-OAB questionnaire was 2.39 ± 0.2. A significant comparison was found between self-reported perception of PFM contraction and symptoms of overactive bladder (p=0.018) and urinary incontinence (p=0.05). Conclusion: There was a high prevalence of women who reported not having knowledge or perception of the PFM. Since the lack of knowledge and perception of the PFM may be related to the development of urogynecological disorders, further studies are needed to implement educational and rehabilitative approaches (if necessary) for the female population.
Keywords: Pelvic Floor; Muscular contraction; Urinary incontinence; Questionnaires